Strategi tranfromasi publik relations pada era digital - syahlatunnisa, syifa (Maliki Interdisciplinary Journal, 2025)
The development of information and communication technology has influenced the practice of Public Relations (PR). This change has shifted communication patterns from one-way to two-way, interactive and participatory. PR practitioners are required to adapt to the developments in the digital era through technology-based, creative, and responsive communication strategies. The use of social media such as Instagram, YouTube, and TikTok plays a crucial role in building image, strengthening reputation, and increasing audience engagement. Furthermore, the use of data analytics helps PR practitioners understand public behavior and preferences more accurately, allowing for targeted communication strategies. Collaboration with digital influencers is also an effective strategy for expanding message reach and building public trust. Therefore, optimizing digital communication strategies is a crucial step to ensure Public Relations practices remain relevant in the technological era.